Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kayu Jawa (Lannea coromandelica (Houtt.) Merr.) Terhadap Bakteri Penyebab Infeksi Kulit Dengan Metode Difusi Agar - Kayla, Aulia Putri; Fitriana, Fitriana; Nuryanti, Siska (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
The purpose of this study was to determine the antibacterial activity of ethanol extract of Java wood leaves (Lannea coromandelica (Houtt.) Merr.) against bacteria that cause skin infections. The research method begins with an extraction process using the maceration method with 96% ethanol solvent and evaporated using a rotavapor. Java wood leaf ethanol extract was screened with a concentration of 0.1%; 0,5%; and 1% against bacteria Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Propionibacterium acnes. MIC and MBC tests were carried out and antibacterial activity tests were continued using the agar diffusion method with a concentration variation of 0.8%; 1,6%; 3,2%; 6,4%; and 12.8%. Screening test results of Staphylococcus aureus bacteria at 0.5% and Propionibacterium acnes bacteria at 0.1%. MIC value against Staphylococcus aureus bacteria at 0.2% and Propionibacterium acnes bacteria at 0.05%. While the MBC value against Staphylococcus aureus bacteria at 0.8% and Propionibacterium acnes bacteria at 1.6%. The results of testing the antibacterial activity of ethanol extract of Java wood leaves against Staphylococcus aureus and Propionibacterium acnes bacteria had the largest inhibitory zone diameter at a concentration of 12.8% of 11.32 mm and 12.83 mm respectively. Based on the results of research, ethanol extract of Java wood leaves has potential as an antibacterial.